Assessing fragile sites in carcinogenic environments: Is this an alert signal? - Stafne, Annwyn Pamela (My University, 2006)
Fragile sites are highly unstable regions of the genome, which have a tendency to form gaps and breaks in metaphase chromosomes under replication stress conditions. There are many common fragile sites in the human genome and exposure to carcinogens may affect several genes localised in fragile sites within a single cell, which could lead to activation of oncogenes and inactivation of tumour-suppressor genes simultaneously. FRA3B on chromosome 3 and FRA16D on chromosome 16 are the two most commonly expressed fragile sites and contain the FHIT and WWOX genes respectively. These genes are tumour suppressor genes and are inactivated in a number of different ways. Carcinogens found in cigarette smoke have been found to increase fragile site expression and could alter the integrity of theses genes in active smokers. Ten healthy non-smoking (control) individuals and twenty active smokers were recruited for the purpose of this study. Fluorescence in situ hybridisation was performed with probes spanning spanning the FHIT gene and RT-PCR was performed to assess both FHIT and WWOX expression. No significant difference in breaks at fragile sites was observed between controls and active smokers in the FISH experiments. In addition, no aberrant transcripts were detected for either FHIT or WWOX with RT-PCR. Although the sampling group was limited and heterogenous, no increase in the expression of breaks at fragile sites was seen in active smokers in the present study.
Student Number : 9901196J - MSc dissertation - School of Pathology - Faculty of Science
Keywords: fragile sites; genome; gaps; metaphase chromosomes; stress conditions; smokers; non-smokers